2016
DOI: 10.1002/pen.24386
|View full text |Cite
|
Sign up to set email alerts
|

Frontal polymerization of superabsorbent polymers based on vermiculite with slow release of urea

Abstract: Poly(acrylic acid-co-acrylamide)/sodium carboxymethyl cellulose/vermiculite (VMT) superabsorbent polymers (SAPs) were prepared by frontal polymerization (FP), a kind of polymerization model characterized by short reaction times and low-energy consumption. The effects of VMT content and monomer ratios on frontal parameters and water absorbency were investigated. Due to the good heat insulation property of VMT, the propagating front still sustained at high VMT concentrations (over 30%). The preparation of SAPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[10][11][12] One of the most promising research lines is the development of biodegradable matrices which contain the required nutrients. [13,14] Nutrients can be supplied gradually to crops through matrix biodegradation, preventing water from dragging excess nutrients toward the subsoil. [15] Biodegradable matrices can be produced from polysaccharides or proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] One of the most promising research lines is the development of biodegradable matrices which contain the required nutrients. [13,14] Nutrients can be supplied gradually to crops through matrix biodegradation, preventing water from dragging excess nutrients toward the subsoil. [15] Biodegradable matrices can be produced from polysaccharides or proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(acrylic acid‐co‐acrylamide)/sodium carboxymethyl cellulose/vermiculite polymers was used as controlled release materials to create a slow‐released urea fertilizer . Most of these coating materials are derived from nonrenewable and nonbiodegradable materials, which can accumulate in soil, degrade soil fertility and possibly release toxic gases during the coating degradation process ,.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that 70-80% of fertilizers were lost through degradation, surface run-off, leaching, and volatilization, etc, which have resulted in poor harvest and signi cant economic loss as well as detrimental environmental impacts [2,3]. Controlled release carriers encapsulate fertilizers in the matrices that can afford to sustain the release of nutrients such as nitrate and potassium to the plants in a sustained manner and could provide higher fertilizer utilization e ciency, reduce nutrient loss, enhance crop yield and minimize environmental pollution [4,5].…”
Section: Introductionmentioning
confidence: 99%